Tay Son Uprising (1771-1802) in Vietnam: Mandated by Heaven? - Ku, Boon Dar (History, Politics & Securities Research Centre, Universiti Kebangsaan Malaysia, 2017)
This article attempts to explore the extent to which the concept of ‘mandate from heaven’ was exploited by the Tay Son brothers to justify their uprising against the Nguyen family in southern Vietnam and the Trinh in the north. The Nguyen and Trinh families each claimed to be the trustee of the Le dynasty of Vietnam. This study traces the background of the Tay Son brothers who triggered the rebellion and explains the legitimacy of their uprising. It is significant to delve into this event as the Tay Son Uprising was the only one in Vietnamese history which brought down a legitimate dynasty, recognised by China. In addition to using secondary sources written by scholars from China, Vietnam and the West, primary sources on genealogy, the royal edicts from the Institute of Sino-Nom Studies and the writings of the Western travellers who had the opportunity to explore Vietnam in the 19th century were consulted.